Analysis of current migration processes in EU countries - Zastavetska Lesia; Заставецька Леся; Zelenska Lyubov; Зеленська Любов; Semehen Oksana; Семеген Оксана; Zastavetskyi Taras; Заставецький Тарас (Видавничий дім «Гельветика», 2025)
Abstract. Relevance of the study: the study of migration processes in the EU countries is relevant, since these processes significantly affect economic development, social integration and cultural diversity of the region. Growing population mobility requires states to adapt policies related to labor migration, refugees and immigrant integration. The analysis of migration trends also allows us to better understand the challenges faced by EU countries and develop effective strategies to overcome them. The subject of the study is migration processes in EU countries in the modern period. Purpose of the study: to study modern migration processes in EU countries, to identify the main trends of modern migration processes in the region, to group EU countries according to the similarity of migration processes in them. Research methodology: a comprehensive scientific approach that combines quantitative and qualitative methods of analysis, statistical analysis methods are applied. The results of the study: the volume and structure of migration in the countries of the European Union in the modern period were analyzed, the gender and age characteristics of modern immigrants and emigrants were indicated and the possible impact of these characteristics on the labor market of the region were analyzed. The latest trends and trends of modern migration processes in the countries of the region were analyzed. The EU countries were classified by the volume of immigration, in particular, 4 groups of countries were identified, namely: countries with the largest number of immigrants; countries with high immigration rates; countries with average immigration rates and countries with the lowest immigration rates. The volume and geography of forced migration of Ukrainians related to military operations since 2022 were characterized. Practical significance: the results of the study reflect the current features of migration processes in the EU region, they can be used for further research and forecasting certain socio-economic parameters, such as: changes in the demographic situation of the EU as a whole and its individual countries, calculations of the demographic burden on the working-age population in the coming years, the study of individual migration trends (educational migration, digitalization, globalization of the labor market, etc.).Conclusions: modern migration processes in the EU countries were studied, changes in immigration, emigration and balance of migration indicators in the countries of the region were established. Countries were grouped according to the similarity of immigration indicators. The volume and geography of Ukrainian migrants in connection with military operations were characterized, and the impact of this type of migration on overall migration indicators in the EU was reflected. Prospects for further research are related to a detailed study of megatrends that influence modern migration processes in the world, including in the countries of the European Union, such as: globalization processes, the impact of wars and military conflicts, environmental factors, educational prospects, etc. An important place in modern research remains for the study of forced migrations of Ukrainians associated with military operations, in particular the volume of refugee flows to various EU countries, the features of social adaptation of Ukrainian citizens in these countries, their impact on the economy and the labor market, etc.

Резюме. Актуальність дослідження: вивчення міграційних процесів у країнах ЄС є актуальним, оскільки ці процеси суттєво впливають на економічний розвиток, соціальну інтеграцію та культурну різноманітність регіону. Щораз більша мобільність населення вимагає від держав адаптації політики, що стосується трудової міграції, біженців та інтеграції іммігрантів. Аналіз міграційних тенденцій також дозволяє краще зрозуміти виклики, з якими стикаються країни ЄС, і розробити ефективні стратегії для їх подолання. Предметом дослідженняє міграційні процеси в країнах ЄС у сучасний період. Мета дослідження: вивчити сучасні міграційні процеси в країнах ЄС, виявити основні тренди сучасних міграційних процесів в регіоні, здійснити групування країн ЄС за подібністю міграційних процесів у них. Методологія дослідження: комплексний науковий підхід, що поєднує кількісні та якісні методи аналізу, застосовано методи статистичного аналізу. Результати дослідження: проаналізовано обсяги та структуру міграцій у країнах Європейського союзу в сучасний період, вказано гендерні та вікові особливості сучасних іммігрантів та емігрантів та можливий вплив цих особливостей на ринок праці регіону. Проаналізовано новітні тенденції та тренди сучасних міграційних процесів у країнах регіону. Здійснено класифікацію країн ЄС за обсягами імміграції, зокрема виділено 4 групи країн, а саме: країни з найбільшою кількістю іммігрантів; країни з високими показниками імміграції; країни із середніми показниками імміграції та країни з найменшими показниками імміграції. Схарактеризовано обсяги та географію вимушених міграцій українців, що пов’язані з військовими діями від 2022 року.Практичне значення: результати дослідження відображають сучасні особливості міграційних процесів у регіоні ЄС, вони можуть бути використані для подальших досліджень та прогнозування певних соціально-економічних параметрів, як-от: зміни в демографічній ситуації ЄС загалом та окремих його країн, розрахунків демографічного навантаження на працездатне населення в наступні роки, вивчення окремих міграційних трендів (освітні міграції, діджиталізація, глобалізація ринку праці тощо). Висновки: досліджено сучасні міграційні процеси в країнах ЄС, встановлено зміни в показниках імміграції, еміграції та сальдо міграцій у країнах регіону. Здійснено групування країн за подібністю показників імміграції. Схарактеризовано обсяги та географію українських мігрантів у зв’язку з військовими діями, відображено вплив цього виду міграцій на загальні міграційні показники в ЄС.
Аналіз сучасних міграційних процесів у країнах ЄС
Весь випуск: https://journals.kmf.uzhgorod.ua/index.php/geograph/issue/view/7
Keywords: geography of migrations; migration processes; emigration; immigration; EU